2017
DOI: 10.1073/pnas.1713458114
|View full text |Cite
|
Sign up to set email alerts
|

Local optical control of ferromagnetism and chemical potential in a topological insulator

Abstract: Many proposed experiments involving topological insulators (TIs) require spatial control over time-reversal symmetry and chemical potential. We demonstrate reconfigurable micron-scale optical control of both magnetization (which breaks time-reversal symmetry) and chemical potential in ferromagnetic thin films of Cr-(Bi,Sb) 2 Te 3 grown on SrTiO 3 . By optically modulating the coercivity of the films, we write and erase arbitrary patterns in their remanent magnetization, which we then image with Kerr microscopy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
(62 reference statements)
0
21
0
Order By: Relevance
“…This is a consequence of the constant Fermi velocity of the linear dispersion, which allows perfect matching of the injected and transmitted waves. Consequently, to attain confinement, one needs to either open a gap by breaking a symmetry in the outer region [21,[33][34][35][36][37][38], or invoke finite-size effects [39].…”
Section: Introductionmentioning
confidence: 99%
“…This is a consequence of the constant Fermi velocity of the linear dispersion, which allows perfect matching of the injected and transmitted waves. Consequently, to attain confinement, one needs to either open a gap by breaking a symmetry in the outer region [21,[33][34][35][36][37][38], or invoke finite-size effects [39].…”
Section: Introductionmentioning
confidence: 99%
“…2,13,16 Indeed, a number of studies using global magnetization measurements 14,17,18 and magnetic force microscopy 19,20 have observed FM-like response in magnetically doped TI thin films. Surprisingly, however, recent scanning SQUID magnetic imaging 21 and transport studies, 22,23 as well as analysis of Kerr microscopy imaging, 24 have suggested the presence of a superparamagnetic (SPM) state in Cr-doped (Bi, Sb) 2 Te 3 films in which instead of a long-range FM order the magnetism is comprised of single-domain magnetic islands. These islands are of characteristic size of few tens of nanometers and are only weakly coupled to each other.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Similarly, the SPM was demonstrated locally in films that do show QAH but at elevated temperatures at which no quantization was present. 21,24 Here we report scanning SQUID-on-tip (SOT) magnetic imaging of modulation-doped (Bi,Sb) 2 Te 3 films performed concurrently with transport measurements that show full QAH quantization. We observe unambiguous SPM behavior both in the magnetization reversal process in the plateau transition regions near H c , as well as within the macroscopically quantized state.…”
Section: Introductionmentioning
confidence: 99%
“…1, A and B) (1,2). Notably, the position of the CES, in contrast to those at the sample edge (3,4,(9)(10)(11)(12)(13)(14) or at the local gate boundary (5-7), can potentially be manipulated via domain control by external fields such as local magnetic field, current-induced spinorbit torque (16,17), or optical illumination (18). Thus, a localized electronic channel based on the CES can be constructed in a reconfigurable manner.…”
mentioning
confidence: 99%